The Influence of Community Culture on the Giving of Colostrum to Infants - Rickiy Akbaril Okta Firdaus; Hakim Tobroni HR; Dewi Retno Puspitosari; Achmad Wahdi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Background: Awareness of the importance of breast feeding colostrum is still low, due to the presence of Culture contributes to the behavior of individuals and groups of people, cultures can menompa health behavior and health may worsen. This study aimed to determine the influence of culture on the provision comunnity colostrum in infants in rural districts Kandat Karangrejo Kediri district. Methods: The design of this study is an analytical cross sectional population of 56 and a total sample of 49 respondents who have a baby aged 7 days - 6 months, which is in the village of Kediri district Kandat Karangrejo districts, with a simple random sampling technique variable in this study consisted of two variables: independent variables which influence the society and culture of the dependent variable, namely the provision of colostrum in children, collect data using culture questionnaire and colostrum. Using chei-square statistical test (p < 0,05). Results: The results of this study, most of the 40 respondents had a positive culture and most of the 45 respondents gave the colostrum to the baby, based on test results che square p value = 0.002 (There is a cultural influence on giving colostrum to babies in Kandat Village, Karangrejo District, Kediri Regency). Discussion: The conclusion of this study is no effect on the provision of public culture colostrum to the baby in the Village District of Kandat Karangrejo Kediri.